Effect of electron radiation dose on wettability and free surface energy of poly(ethylene terephthalate) film - Żenkiewicz, M. (Polimery, 2022)
Results of investigation of the effect of electron radiation dose (up to 500 kGy), generated in linear high voltage accelerator, on the contact angle and surface free energy of poly(ethylene terephthalate) (PET) film were presented. Water, glycerin, formamide, diiodomethane, alpha-bromonaphthalene as well as their two- or three-component systems were used as measurement liquids. Calculations were done according to Owens-Wendt's or van Oss-Chaudhury-Good's methods, using the results of contact angle measurements. Tests of wettability of samples investigated have been also done. It was found that the courses of changes of contact angle, decreasing with an increase in radiation dose, were similar for all measurement liquids used although significant quantitative differences appeared (Fig. 1, Table 4). The largest changes of contact angle values were observed for radiation doses up to 50 kGy. Surface free energy results, obtained by each method or on the basis of the contact angle with liquids from particular measurements systems used in the same method, differed in general in the whole range of doses used (Figs. 2-6, Tables 5-8). For this reason surface free energy can not be treated as absolute measure of thermodynamic state of surface layer of radiation modified PET film. Its values can be compared only in the case when they are determined by the same method and with the same measurement liquids (or standard ones) using.